Single-Level Minimally Invasive Transforaminal Lumbar Interbody Fusion versus Anterior Lumbar Interbody Fusion with Posterior Instrumentation at L5/S1 - Jacob, Kevin C.; Patel, Madhav R.; Ribot, Max A.; Parsons, Alexander W.; Vanjani, Nisheka N.; Pawlowski, Hanna; Prabhu, Michael C.; Singh, Kern (World neurosurgery, 2022)
To compare outcomes between minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) and anterior lumbar interbody fusion (ALIF) at L5/S1. Primary, elective, single, MIS-TLIF, or ALIF with posterior fixation at L5/S1 were identified. Patient-reported outcome measures (PROMs) were collected. Coarsened exact matching was used to control for significant differences. Achievement of minimum clinically important difference [MCID] was determined by comparing ΔPROM scores with threshold values. Demographic/perioperative characteristics were compared between MIS-TLIF and ALIF cohorts using χ2 Student t tests. Differences in mean PROM scores, MCID rates, and postoperative complications were evaluated using an unpaired t test. After coarsened exact matching, 93 patients received MIS-TLIF and 50 received ALIF. Cohorts differed in operative time, estimated blood loss, and postoperative narcotic consumption on postoperative day 0 (P < 0.034, all). Mean PROMs differed significantly on 12-Item Short-Form Physical Component Summary at 6 weeks and 1 year, Patient-Reported Outcomes Measurement Information System Physical Function at 6 weeks, Oswestry Disability Index at 6 weeks, and visual analog scale (VAS) back at 6 weeks, with the ALIF cohort showing significantly improved mean PROMs (P ≤ 0.044, all). Significantly greater rates were reported of MCID achievement for PROMs for the ALIF cohort: VAS back at 6 weeks, Oswestry Disability Index at 12 weeks, 12-Item Short-Form Physical Component Summary at 6 weeks, and Patient-Reported Outcomes Measurement Information System Physical Function at 12 weeks (P ≤ 0.047, all). A greater rate of MCID achievement for the MIS-TLIF cohort was seen for 6-week and overall VAS leg (P < 0.046, all). Postoperative fever was greater in the TLIF cohort (9.6% vs. 2.0%; P < 0.047). Patients undergoing ALIF showed significantly improved rates of MCID achievement for disability, physical function, and back pain during the early postoperative period. However, the overall MCID achievement rate for leg pain was higher for the MIS-TLIF cohort.